0=-2(u+-1)u=

Simple and best practice solution for 0=-2(u+-1)u= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=-2(u+-1)u= equation:



0=-2(u+-1)u=
We move all terms to the left:
0-(-2(u+-1)u)=0
We add all the numbers together, and all the variables
-(-2(u-1)u)+0=0
We add all the numbers together, and all the variables
-(-2(u-1)u)=0
We calculate terms in parentheses: -(-2(u-1)u), so:
-2(u-1)u
We multiply parentheses
-2u^2+2u
Back to the equation:
-(-2u^2+2u)
We get rid of parentheses
2u^2-2u=0
a = 2; b = -2; c = 0;
Δ = b2-4ac
Δ = -22-4·2·0
Δ = 4
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{4}=2$
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-2}{2*2}=\frac{0}{4} =0 $
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+2}{2*2}=\frac{4}{4} =1 $

See similar equations:

| (-7,1);m=5 | | 7.7i=76.23 | | 18+h≥=13 | | 16=4(a+1)+2a | | 2/3t=-52 | | -3.39-3.4d=-1.1d+11.08 | | 4x(7)=15 | | 1−–3r=–14 | | (3x=12)=72 | | 6y2+9y=6 | | 4p−4=16 | | |2x+1|=(4x-7) | | 2q-q-q+2q=18 | | 6x-7=x+30 | | 3+2d=9d= | | 3m-m-m+4m+4m=9 | | 13y–18=2 | | y13y–18=2 | | 6x-7=x=x+30 | | 16y=309 | | 0.08/0.5=0.24/x | | 6v+2v-6v=6 | | 9(63)=x2 | | y/11=19 | | 2(1-5r)=-2r+4 | | 18y-17y-y+4y=8 | | -4y+4=2y-20 | | 8x-12=3x+8+8x-2 | | 3c–6+3c=30 | | 2x+x+42=147 | | -8+2m-2m=9 | | (5x)+(4x+27)=180 |

Equations solver categories